2013
DOI: 10.1172/jci65856
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial stem cell mutations that promote squamous cell carcinoma metastasis

Abstract: Squamous cell carcinomas (SCCs) originate in stratified epithelia, with a small subset becoming metastatic. Epithelial stem cells are targets for driver mutations that give rise to SCCs, but it is unknown whether they contribute to oncogenic multipotency and metastasis. We developed a mouse model of SCC by targeting two frequent genetic mutations in human SCCs, oncogene Kras G12D activation and Smad4 deletion, to mouse keratin 15-expressing (K15 + ) stem cells. We show that transgenic mice developed multilinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(138 citation statements)
references
References 61 publications
(98 reference statements)
7
130
1
Order By: Relevance
“…However, it was not known whether CSC regulatory mechanisms change during disease progression, correlating with the enhanced recurrence and metastasis of high-grade SCCs (1), which could influence the selection of the most efficient therapy. In the study reported here, we generated lineages of SCC progression and showed that a high percentage of WD-SCCs exhibiting epithelial features progressed to PD and mesenchymal SCCs with enhanced metastasis capability, recapitulating the skin SCC progression reported in other mouse models (42). In contrast, previous reports suggested that spindle and EMT-like skin SCCs might arise by a route other than WD-SCCs after DMBA/TPA treatment, relying on a different cell of origin and/or lower requirement for inflammatory stimuli (22).…”
Section: Discussionsupporting
confidence: 63%
“…However, it was not known whether CSC regulatory mechanisms change during disease progression, correlating with the enhanced recurrence and metastasis of high-grade SCCs (1), which could influence the selection of the most efficient therapy. In the study reported here, we generated lineages of SCC progression and showed that a high percentage of WD-SCCs exhibiting epithelial features progressed to PD and mesenchymal SCCs with enhanced metastasis capability, recapitulating the skin SCC progression reported in other mouse models (42). In contrast, previous reports suggested that spindle and EMT-like skin SCCs might arise by a route other than WD-SCCs after DMBA/TPA treatment, relying on a different cell of origin and/or lower requirement for inflammatory stimuli (22).…”
Section: Discussionsupporting
confidence: 63%
“…A223-LG was derived from a mouse model of SCC with oncogene Kras (G12D) activation and Smad4 deletion in the epithelial progenitors. 45 We found that A223-LG-transplanted cancer exhibits significantly accelerated tumor growth in CD24 ¡/¡ mice comparing with CD24 C/¡ mice (Figs. 7A and B), which is consistent with the observation we made in the 4-NQO oral cancer model.…”
Section: Cd24 ¡/¡ Mice Have An Increase In Myeloid-derived Suppressormentioning
confidence: 67%
“…It was derived from transgenic mice that expressed a constitutively active Kras G12D mutant and simultaneous deletion of Smad4 in the epithelial progenitor cells. 45 Cells were cultured in DMEM supplemented with 10% FBS and 1% penicillin/streptomycin. After two passages, 1.5 £ 10 4 cells in 25 mL sterile 1X PBS were injected in the right lateral side of the tongue of CD24 C/¡ and CD24 ¡/¡ mice.…”
Section: A223-lg Orthotopic Oral Cancer Modelmentioning
confidence: 99%
“…Finally, the remaining 20 publications [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] were combined in the meta analysis and the selection process presented by a flow chart which is shown in Fig. 1.…”
Section: Screening Of the Literaturementioning
confidence: 99%